Strukturasi Makna Budaya dalam Kepemimpinan Adat Melayu, Sakai, dan Talang Mamak untuk Tata Kelola Hutan Riau - Eno Suwarno; M. Rawa El Amady (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2026)
The province of Riau presents a paradox between economic growth and deforestation, a conflict rooted in the struggle between the forest as an extractive space and a culturally meaningful place. This systematic review analyzes how cultural meaning systems are structured within the indigenous leadership of three Riau communities, Malay, Sakai, and Talang Mamak, and how these meanings are reproduced or transformed in forest governance. Integrating Clifford Geertz's interpretive anthropology with Anthony Giddens' structuration theory, we synthesized 68 academic documents published between 1973-2026. The analysis reveals three leadership typologies: hierarchical-genealogical (Malay), centered on sako datuk titles and the "adat basandi syarak, syarak basandi Kitabullah” philosophy; communal-personalistic (Sakai), rooted in place-based ecological knowledge, as seen in Imbo Ayo Customary Forest management; and spiritual-ecological (Talang Mamak), manifested in melambas rituals and forest zoning like rimbo pusaka. The reproduction of these meanings depends on key structuration mechanisms, knowledge-based conflict resolution, and intergenerational enskillment. However, this process faces challenges from state-induced authority fragmentation, aggressive land grabbing due to oil palm expansion, and a regeneration crisis exacerbated by out-migration. In response, communities exercise innovative agency through legal hybridization (e.g., using district decrees to formalize adat territory) and cosmological translation (e.g., reframing rimbo larangan as conservation areas). Yet these strategies carry significant risks of co-optation and cultural erosion when state logic overrides customary flexibility. The study concludes that effective forest governance policies must move beyond legal recognition to actively support local meaning structuration processes while acknowledging internal complexities and political-economic constraints.